Analysis of the nuclear proteome of the resurrection plant Xerophyta viscosa (Baker) and its response to dehydration stress - Abdalla, Kamal O (Department of Molecular and Cell Biology, 2014)
Xerophyta viscosa Baker (family Velloziaceae) can survive extremes of dehydration (desiccation), down to 5% relative water content (RWC) and resumes full physiological activity within 80 h of rehydration. A thorough understanding of this phenomenon may provide further insight into possible mechanisms for improving drought tolerance in other plants. In this respect a comprehensive analysis of the nuclear proteome of this plant and its response to dehydration stress at 35% RWC was carried out. The RWC at 35% represents a distinct phase of the dehydration process where induction of late protection mechanisms is initiated and is a characteristic of desiccation tolerant species. We optimized nuclei isolation and nuclear protein extraction protocols and successfully employed these protocols to isolate highly purified nuclei and subsequently nuclear proteins from fully hydrated and dehydrated X. viscosa leaf samples. The integrity of the purified nuclei was confirmed with light and fluorescent microscopy. The nuclei were uniform spheres, approximately 5 Î¼m in size. The purity and enrichment of the nuclear proteins were confirmed by chlorophyll assay and Western blot analysis. The nuclear proteins were investigated using two-dimensional (2D) and isobaric tags for relative and absolute quantitation (iTRAQ) technologies. Using the 2DE approach, a total of 438 proteins spots were reproducibly detected and analysed of which 18 protein spots were shown to be up-regulated in response to dehydration. These proteins contained both regulatory and functional proteins. The largest category comprised five novel protein factors and two proteins with unassigned functions. The second category comprised proteins involved in gene regulation and signal transduction. The third category comprised stress responsive proteins with chaperone type activities. Other categories include proteins involved in energy metabolism, protein degradation and translation. These results demonstrate that dehydration was controlled by multiple genes within the plant nucleus and X. viscosa may possess its own specific nuclear proteins that are involved in desiccation stress. In addition we comprehensively analyzed the nuclear proteome of X. viscosa using iTRAQ with two-dimensional liquid chromatography and tandem mass spectrometry to complement the data obtained from the 2DE approach. Using iTRAQ, we reproducibly University of Cape Town identified 128 proteins with confidence ¥ 95% (Ï < 0.05). Sixty six percent of the identified proteins showed consistent expression levels. The remaining 34% proteins showed significant changes in expressions. Of the latter, 23% were shown to be up regulated in response to dehydration stress. The remaining 11% were shown to be down regulated. The nuclear proteins of X. viscosa up-regulated in response to dehydration stress showed a coordinated response involving both regulatory and functional proteins and were implicated in diverse cellular functions. The characteristic feature of the X. viscosa nuclear proteins is the high level of stress molecules among the dehydration responsive proteins with evident functions in defense mechanisms compared to down regulated proteins and proteins showing consistent expression levels. These results demonstrate that enhanced defense capacity is crucial to desiccation tolerance and strongly support the notion that late dehydration responsive proteins are involved in protection of the cellular structures during dehydration. Proteins showing consistent expression levels during dehydration most likely maintain the minimum viability in cells under all conditions or may be indirectly associated with desiccation tolerance. Down-regulated proteins are likely important for plant survival under normal growth conditions. The proteins up-regulated in response to dehydration stress were assumed to be associated directly with the acquisition of desiccation tolerance. The up-regulated proteins were further categorized into nine functional groups to gain more insight into their roles in desiccation tolerance. The largest group was shown to be involved in gene regulation and signal transduction (36%), which reflects the role of the nucleus in gene expression and regulation. The second group included stress responsive molecules such as antioxidants, molecular chaperones and compatible solutes (33%). This reflects the importance of strong defense systems in preventing lipid peroxidation, protein aggregation, membrane leakage and maintaining the integrity of cellular structures during dehydration and in the dried state. The third group contained proteins involved in nucleocytoplasmic transport (10%). This might reflect the capacity of this plant to control the movement of molecules to and from the nucleus during dehydration and the importance of this process in adaptation to dehydration stress. The fourth group contained proteins involved in protein translation (7%). Proteins categorized to other functions, include proteins with miscellaneous and unknown functions. Proteins with unknown functions were considered to be X. viscosa nuclear-specific proteins. There was good correlation between the up-regulated proteins identified by 2-DE and iTRAQ approaches. In conclusion, this study revealed that X. viscosa nuclear proteome was responsive to dehydration stress and desiccation tolerance is University of Cape Town genetically encoded. Secondly, X. viscosa relies on readily inducible protection to combat desiccation and desiccation tolerance is controlled by multiple genes within the plant nucleus. Thirdly, the protective mechanisms of desiccation tolerance utilized by X. viscosa appear to involve signal perception genes and modulating gene expression of appropriate genes encoding protective molecules including antioxidants, molecular chaperones, compatible solutes, proteins of translation and degradation machinery, proteins with miscellaneous functions and novel protein factors. Lastly, proteins are crucial to desiccation tolerance allowing X. viscosa to possess a unique stress tolerance with versatile and coordinated actions to provide protection for its cellular structures during desiccation and in the dried state. To our best knowledge this is the first study to provide insight into the nuclear (organellar) proteome of a desiccation tolerant plant.